Public broadcasting and social media challenges from the point of view of journalists A field study in public broadcasting channels in Iraq - Dr. Ahmed Abd Hussein (Genius Journals, 2023)
This research presents, through its problem, objectives, and methodological procedures, a current vision of the extent of the challenge faced by journalists working in public channels in the face of media developments. Especially social networking sites that have developed over the past years and affected the audience of public channels. The study has reached important results, for example. 1. Lack of interaction with public broadcasting channels compared to social networking sites leads to a weak impact of public channels on the media audience. 2. The study also showed that there is a polarization of the public broadcasting audience in favor of social media. 3. Most of the respondents acknowledged that there is competition between public broadcasting and social networking sites. This is in addition to many other search results.
Keywords: public broadcast; social media; Media Jobs